Serologic Responses After Hepatitis B Vaccination in Preterm Infants Born to Hepatitis B Surface Antigen–Positive Mothers: Singapore Experience. Issue 8 (August 2017) - Tan, Christelle Xian-Ting; Chan, Si-Min; Lee, Le-Ye; Ong, Christina; Phua, Kong-Boo; Aw, Marion Margaret; Saw, Sharon; Lee, Guan-Huei; Wong, Franco; Thoon, Koh-Cheng
Abstract : Background: The Advisory Committee on Immunization Practices (ACIP) recommends a 4-dose vaccination schedule for preterm low birth weight infants (<2 kg) and a 3-dose vaccination schedule for preterm infants (≥2 kg) born to hepatitis B surface antigen (HBsAg)-positive mothers. However, data remain limited for these high-risk infants, and the optimal dosing schedule in Asia is not well established. Aim: The aim of this study was to evaluate the serologic vaccine responses in preterm infants born to HBsAg-positive mothers using current vaccination guidelines. Methods: Preterm babies of gestation less than 37 completed weeks born to HBsAg-positive mothers were prospectively recruited during 6 years (June 2009 to December 2015) and retrospectively recruited via convenience sampling in 2 years (June 2013 to April 2015) in 2 tertiary pediatric centers. The preterm infants were given 4 or 3 vaccine doses as per ACIP 2005 guidelines. Vaccine response was defined as achieving hepatitis B surface antibody values of >10 IU/L [Abbott Architect (Abbott Laboratories, Chicago, IL)] at 9 months of chronologic age. Results: A total of 24 preterm infants were recruited. Four had a birth weight <2 kg. Of 23 surviving infants, all were negative for HBsAg. One baby (4.5%) did not achieve adequate vaccine response. All 4 infants with birth weight <2 kg achieved seroprotective values. Conclusion: The current ACIP-recommended vaccination schedule results in adequate antibody responses in preterm infants of HBsAg-positive mothers.